Anion-controlled structural motifs in cadmium coordination polymers: Formation of linear chain versus triple-stranded ladder. (1st October 2019) - Notash, Behrouz; Rodbari, Mona Farhadi
Graphical abstract: Three novel coordination polymers [CdL(NCS)2 (DMSO)2 ] n (1 ), {[Cd3 L3 (OAc)4 (NCS)2 ](DMSO)2 ]} n (2 ) and [CdL(µ-SeCN)2 ] n (3 ) were synthesized using ligand 1, 4-bis(4-pyridyl)-2, 3-diaza-1, 3-butadiene (L ) and different cadmium salts. The results show that anions play a cardinal role in the final structural motif of these coordination polymers. We also investigated the role of solvents on the morphology of compound1 . Abstract: Three novel coordination polymers [CdL(NCS)2 (DMSO)2 ] n (1 ), {[Cd3 L3 (OAc)4 (NCS)2 ] (DMSO)2 ]} n (2 ) and [CdL(µ-SeCN)2 ] n (3 ) have been synthesized by using exoditopic N -donor Schiff base ligand 1, 4-bis(4-pyridyl)-2, 3-diaza-1, 3-butadiene (L ) in the presence of different cadmium salts. The results show that anion has an important role in the formation of different structural motif. X-ray structural analysis shows that in these cases 1D linear chain, 1D triple-stranded ladder and 2D structural motifs have been formed for compound1, 2 and3, respectively. Our results showed that solvent type affect morphology of compound1 .